KOMUNIKASI PERSUASIF TIM ADIWIYATA SDN 6 PEKANBARU DALAM MEWUJUDKAN SEKOLAH ADIWIYATA - Saputri, Mayang; Awza, Rusmadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Adiwiyata program is a program that implemented in school to actualize caring attitude and environment cultured on student. This program launched for the first time on 2006 by government through ministry of environment. SDN 6 Pekanbaru was success achieve three Adiwiyata awards in just two years period.AdiwiyataTeam running this program by using persuasive communication toward students by giving encouragement and example of impelementationabout caring attitude and cultured environment. This research aims to find out persuader credibility, persuasive message, and effect that camefrom the persuasive communiacation of SDN 6 PekanbaruAdiwiyata Team on actualizeAdiwiyata School.This research using qualitative research method with descriptive approach. The subject of this research was choosing by purposive technique who consists of Head Master, Chief of Adiwiyata Team, student guardian who are joined in Adiwiyata Team and students of SDN 6 Pekanbaru. Data was collected through interview, observation and documentation. Data was analyst using Interactive model of Miles & Huberman. To achieve the validity of the data in this study, researcher used the triangulation technique.According to the research’s result, SDN 6 PekanbaruAdiwiyata Team has credibility as communicatorwhich is expertness that get from socialitation and workshop with another school and also their knowledge about environment. AdiwiyataTeam also has trust worthiness by implement caring attitude and environment cultured. Persuasive messege consists of verbalmessege that includes clarity, simplicity and accuracy. Meanwhile nonverbal messege includes giving example of environment caring behavior such practice how towashing hands correctly, saving water and electricity, and also utilize second stuff that recycle into vase, pensil case and screen.Effect that produced consists of three parts, first is cognition, there are increasing, understanding, and awareness on students about environment from information that given by Adiwiyata Team. Second is affection, students start to have caring attitude of environment. Third is conation, there is action from students to keep environment such put trash in it’s place and saving water.Key Words : persuasive Communication, Adiwiyata Program, Communication Model of Applebeum and Anatol